Alkylphospholipids - A Promising Class of Chemotherapeutic Agents with a Broad Pharmacological Spectrum - Juliana de Almeida Pachioni; Juliana Gallottini Magalhães; Elys Juliane Cardoso Lima; Luciana de Moura Bueno; Joyce Ferreira Barbosa; Matheus Malta de Sá; Carlota Oliveira Rangel-Yagui (Frontiers Media S.A., 2013)
PURPOSE: Since when alkylphospholipds (ALPs) were discovered and, even further after miltefosine's approval for the treatment of cutaneous metastasis of breast cancer and leishmaniasis, their activity against many other diseases have been extensively studied. This review aims to provide a summary of the alkylphospholipids' applications investigated so far. RESULTS: The mechanism of action of ALPs is not fully understood, however it is believed that they interfere with lipid homeostasis leading to cell apoptosis. Due to ALPs cytotoxic activity, this class of molecules has shown to be effective against many diseases and conditions. Besides the approval of miltefosine for application in cutaneous metastasis of breast cancer and visceral and cutaneous leishmaniasis, several other analogs have proved efficacy and are promising as less toxic alternatives. ALPs have also shown in vitro and in vivo activity against Trypanosoma spp., amoebae, Tricomonas vaginalis, Schistosoma mansoni, HIV, and some fungi and bacteria species. The use of ALPs for intraocular lens coating is also under investigation. In addition, a clinical trial comparing miltefosine with usual treatments to spontaneous urticaria is also being conducted. CONCLUSIONS: Alkylphospholipids present such a broad pharmacological spectrum that justifies the need for further investigations of the drug class mechanisms of action, as well as the search for new analogs with improved activity and toxicological profiles. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.